THE ROLE OF ACCOUNTING INFORMATION SYSTEM ON HUMAN CAPITAL AND FINTECH TO IMPROVE MSMEs PERFORMANCE - Winarsih, Winarsih; Zulfikarianti, Ratna; Fuad, Khoirul (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2024)
This research aims to examine the factors of the role of accounting information systems in mediating the relationship between human capital and financial technology (fintech) on MSMEs performance in the digital era. The population in this study is the owner of MSMEs in the city of Semarang, Indonesia. This study used purposive sampling method. A total of 125 MSMEs were tested for the regression relationship of the four constructs. This study found the positive influence of human capital and accounting information systems on MSMEs performance. However, financial technology has no effect on MSMEs performance. In addition, the positive influence of human capital and financial technology on accounting information systems was found. Mediation analysis shows that accounting information systems play a role in bridging the relationship between financial technology and MSMEs performance. However, accounting information systems do not play a role in bridging the relationship between human capital and MSMEs performance.